Knowledge, attitude and practice on organ donation and transplantation among doctors in anesthesia and intensive care unit : designing and validation of a new questionnaire study - Lim, Keren Seok Luan (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Organ shortage remains the major concern not only in Malaysia but globally and the number of those who needs organ transplantation are increasing over the years. Healthcare professionals especially doctors play a pivotal role in early identification of potential organ donors and thus, the study aims to validate a newly construct questionnaire regarding knowledge, attitude and practice among doctors working in the Anesthesia and Intensive Care Department on organ donation and transplantation in order to gain a baseline information to which future improvement programmes could be planned. The constructed questionnaire had 3 main domains and a total of 38 items along with demographic questions. Three experts in the field of organ donation and transplantation were invited for content validity through reviews. Construct validity was established by exploratory factor analysis (EFA), whereas internal consistency was checked by Cronbach's Alpha. Statistical analysis was performed by SPSS version 25 (IBM, New York, USA) as well as using Microsoft Excel 2016. A total of 200 respondents of various demographic representations responded to the questionnaire. Three content experts deemed the questions to be valid in its content via reviews. Difficulty index was easy at 72.8% with the discrimination index at 0.31 showing good discriminant property of the questionnaire. The Kuder-Richardson 20 shows that the knowledge component is not reliable as the value was 0.34 carrying a standard deviation of 1.78 with a small margin of standard error of measurement at 1.44. Kaiser-Meyer-Olkin Measure of Sampling Adequacy and Bartlett Test of Sphericity was 0.868 and p<0.001 respectively which merits the data to be suitable for exploratory factor analysis. Scree plot shows an existence of 2 distinct factors in the data set of interest. 3 question stems were deleted and the extracted data was divided into Attitude (5 stems) and Practice (16 stems) which carries commonalities of 0.158 – 0.259 and 0.124 – 0.658 respectively. The question stems showed good discriminant validity at 0.308. With regards to internal consistency, the attitude component had Cronbach Alpha of 0.56 (not reliable) and practice component had Cronbach Alpha of 0.91 (very reliable). This study has answered the research questions posed. The knowledge component of the study although was easy in nature and has good discriminating capability, it had a poor internal reliability but was confounded by many factors of which heterogeneity of the participants was the main issue. The attitude and practice question stems are found to be highly discriminant. The attitude did not have adequate internal consistency but it was confounded by the reduced number of question stems while the practice component was highly reliable. Further work would be needed to fine tune the questionnaire in the future to solve the issues highlighted.